Entre tradição e inovação: um estudo sobre mudanças no ensino de gramática em livros didáticos brasileiros de Língua Portuguesa - Alexsandro da Silva; Artur Gomes de Morais (Universidade do Minho, 2011)
The purpose of this article is to investigate the treatment given to grammar teaching or to the linguistic analysis in three Brazilian collections of Portuguese textbooks approved by the 2007 National Textbook Program. The results point out that two of the analyzed collections used the term grammar and all of them tended to establish educational objectives related to the mastery of the grammar or the language themselves. Regarding the contents, we verified that the traditional topics of school grammar shared the stage with other contents. As we analyzed the activities, we found, in two of the collections, few analytical activities when it came to the traditional contents. At the teaching of the word classes and spelling, we found two main innovations, the use of texts and the tendency to the non-presentation of ready information. At the exploration of the characteristics of textual genders, in addition to using pseudo-texts, the collections adopted, sometimes, a transmissive approach.